The development of vocabulary and morphological awareness: A longitudinal study with college EFL students. (22nd April 2019) - Jiang, Yih-Lin Belinda; Kuo, Li-Jen
Abstract: While the relationship between vocabulary, morphological awareness, and reading comprehension has been examined extensively, research on this relationship among adult second language learners has only been explored recently. The present study addresses this gap by examining how adult English as a foreign language learners developed different types of English vocabulary and morphological awareness over the course of one academic year. Participants included 523 college freshmen in Taiwan with varying reading proficiency levels. Results from a series of mixed-measure analyses of variance revealed that (a) even the more proficient college English as a foreign language learners failed to fully grasp morphological principles; (b) the gap in vocabulary between the less skilled readers, the average, and the skilled readers widened significantly over the course of one academic year; (c) the effect of phonological and orthographic changes involved in morphologically complex words differed for the assessment of base meaning, but did not vary across proficiency levels; (d) progress in different aspects of morphological awareness, such as interpreting the meaning of the suffix or identifying the base of a morphologically complex word, varied significantly among readers of different proficiency levels; and (e) suffixes of different parts of speech posed different challenges to learners. Theoretical and pedagogical implications of the findings are discussed.